Contested Interiority: Sense of Outsideness/Insideness Conveyed through Everyday Interactions with University Campus Doors - Lisa Stafford (Interiority, 2019)
Our sense of place in the world is mediated through our everyday interactions with both people and space (Seamon, 1985). Everydayness is one of the most profound levels and shapers of human experience, yet too often this level of relation is overlooked and taken for granted in the design of environments (Dyck, 2005; Tuan, 1977). In this article, I present a first-person phenomenological account of my everyday interactions with doors on a university campus to uncover contested notions of interiority. My body-space routines reveal how a sense of outsideness/insideness is controlled through my interactions with objects such as doors, door handles and thresholds. These accounts suggest that given our everyday activities are intrinsically linked to designed environments (Upton, 2002) and that interiority is relational (Atmodiwirjo & Yatmo, 2018), adopting an everydayness frame from diverse users’ perspectives is imperative to improve human experiences and spatial justice within design practice. This is critically important for non-normative bodies like mine whose subjective experience of interiority is constantly being disputed and denied by hostile materiality.